The role of a sustainable value chain in reducing production costs in the economic unit (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:          The research aims to clarify the cognitive foundations of the sustainable value chain and its role in reducing production costs within the economic unit. The researchers relied on the application of sustainable value chain technology to the stages of electric heater production 120 l, the research sample within the National Electrical Industries Company for the year (2022). To achieve this, the researchers relied on the inductive and deductive approaches, and they reached many conclusions, the most important of which was that the use of a sustainable value chain reduces emissions and waste. The resulting result protects raw materials from waste and waste and increases the rate of utilization of those materials by reusing them more than once, which helps to achieve optimal use of resources, which in turn leads to reducing costs within the unit.